PENGARUH METODE OUTDOOR STUDY TERHADAP PENINGKATAN HASIL BELAJAR SISWA KELAS III SD MATERI PROFESI DAN PEKERJAAN - Nur Alfiyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the influence of the outdoor study method on the improvement of learning outcomes of grade III elementary school students on professional and occupational materials. The research was carried out at Al Khalifah Integrated Islamic Elementary School Jombang using a quantitative approach through a pre-experimental one-group pretest-posttest design. The research subjects consisted of 25 grade III students who were selected using the purposive sampling technique. Data analysis used the Shapiro-Wilk normality test and the Paired Sample t-test hypothesis test. The results showed a significant difference between pre-test and post-test scores with a mean difference of 21,600 (p < 0.001), a standard deviation of 5,902, and a confidence interval of 95% in the range of 19,164 to 24,036. These findings indicate that the application of the outdoor study method has a significant effect on improving student learning outcomes in professional and occupational materials. This research contributes to the development of effective learning methods in the context of the implementation of the Independent Curriculum, especially in utilizing the school environment as a contextual learning resource and supporting the development of holistic competencies of elementary school students.